Selenium Nanoparticles as a Natural Antioxidant and Metabolic Regulator in Aquaculture: A Review - Mahmoud A. O. Dawood; Mohammed F. El Basuini; Sevdan Yilmaz; Hany M. R. Abdel-Latif; Zulhisyam Abdul Kari; Mohammad Khairul Azhar Abdul Razab; Hamada A. Ahmed; Mahmoud Alagawany; Mahmoud S. Gewaily (MDPI AG, 2021)
Balanced aquafeed is the key factor for enhancing the productivity of aquatic animals. In this context, aquatic animals require optimal amounts of lipids, proteins, carbohydrates, vitamins, and minerals. The original plant and animals' ingredients in the basal diets are insufficient to provide aquafeed with suitable amounts of minerals. Concurrently, elements should be incorporated in aquafeed in optimal doses, which differ based on the basal diets' species, age, size, and composition. Selenium is one of the essential trace elements involved in various metabolic, biological, and physiological functions. Se acts as a precursor for antioxidative enzyme synthesis leading to high total antioxidative capacity. Further, Se can enhance the immune response and the tolerance of aquatic animals to infectious diseases. Several metabolic mechanisms, such as thyroid hormone production, cytokine formation, fecundity, and DNA synthesis, require sufficient Se addition. The recent progress in the nanotechnology industry is also applied in the production of Se nanoparticles. Indeed, Se nanoparticles are elaborated as more soluble and bioavailable than the organic and non-organic forms. In aquaculture, multiple investigations have elaborated the role of Se nanoparticles on the performances and wellbeing of aquatic animals. In this review, the outputs of recent studies associated with the role of Se nanoparticles on aquatic animals' performances were simplified and presented for more research and development.